2018
DOI: 10.1080/1828051x.2018.1466665
|View full text |Cite
|
Sign up to set email alerts
|

Average daily gain rates determine eye muscle area and rump fat depth of beef heifers

Abstract: In cow-calf beef production systems, the growth and development of replacement heifers deserve special attention because they affect the age at puberty and the onset of reproductive activity. Therefore, the objective of this study was to test if changes in average daily gain (ADG) have an effect on eye muscle area, rump fat depth and back-fat thickness in developing beef heifers. These traits of 42 beef heifers were measured over time. The results of the current study allow inferring that heifers older than 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The ADG reflects the weight gain of cattle per unit of time. ADG is not only an important factor affecting the number of days of the fattening period [ 7 ], but also affects muscle and adipose tissue growth [ 30 ]. Reynolds et al [ 31 ] found that the ADG could be used as an immune indicator to evaluate the physical condition of cattle, wherein the higher the ADG of the cattle, the lower the immune response in the body and the better the health of the cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The ADG reflects the weight gain of cattle per unit of time. ADG is not only an important factor affecting the number of days of the fattening period [ 7 ], but also affects muscle and adipose tissue growth [ 30 ]. Reynolds et al [ 31 ] found that the ADG could be used as an immune indicator to evaluate the physical condition of cattle, wherein the higher the ADG of the cattle, the lower the immune response in the body and the better the health of the cattle.…”
Section: Discussionmentioning
confidence: 99%